Epidemiology and management of head injury in paediatric age group in North-Eastern Nigeria - J Y Chinda (African Journal of Paediatric Surgery, 2013)
Background: Paediatric head injury (HI) is the single most common cause of death and permanent disability in children world over, and this is increasingly becoming worrisome in our society because of increased risks and proneness to road traffic accidents on our highways and streets. The study set to determine causes and management of HI among children in our society. Patients and Methods: A retrospective review of all children aged 0-15 years with traumatic head injury (THIs) who were managed at the University of Maiduguri Teaching Hospital between July, 2006 and August, 2008. Results: A total of 45 children with THIs presented to the casualty unit of the hospital; 30 (66.7%) were boys and 15 (33.3%) were girls. Three (6.7%) children were less than 1 year of age, 21 (46.7%) were between 1 years and 6 years while 16 (35.6%) and 5 (11.0%) were aged 7-11 years and 12-15 years respectively. Thirty six (80.0%) of the children were pedestrians, 6 (13.4%) fell from a height, while 2 (4.4%) and 1 (2.2% were as a result of home accident and assault, respectively. Twenty one patients (46.7%) had mild HI, while 53.3% had moderate to severe category. Forty one (91.1%) of children were managed as in-patients, mostly (95.1%) by conservative non-operative management, while 4 (8.9%) were treated on the out-patient basis. The mortality rate was 17.8%. Conclusion: H1 among children is of a great concern, because of its incremental magnitude, due to increasing child labour and interstate religious discipleship among children, with attendant high mortality and permanent disabilities. Necessary laws and legislations should be formulated and implemented with organized campaigns and public enlightenment to prevent and mitigate this menace.